2022
DOI: 10.3390/cancers14061444
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of Ion Channels and Their Correlation with Epithelial to Mesenchymal Transition in Breast Cancer

Abstract: Uncontrolled growth of breast cells due to altered gene expression is a key feature of breast cancer. Alterations in the expression of ion channels lead to variations in cellular activities, thus contributing to attributes of cancer hallmarks. Changes in the expression levels of ion channels were observed as a consequence of EMT. Additionally, ion channels were reported in the activation of EMT and maintenance of a mesenchymal phenotype. Here, to identify altered ion channels in breast cancer patients, differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Among the enriched biological processes, positive regulation of membrane potential is a key process in cancer progression with relevance for EMT. EMT has been reported to be dependent on modulation of ion channels of sodium, potassium, and calcium in different cancer types, and inhibiting the activity of these ion channels has been proposed as a potential therapy against cancer progression [ [144] , [145] , [146] , [147] ]. Similarly, G1/S transition is a major checkpoint in the regulation of the cell cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Among the enriched biological processes, positive regulation of membrane potential is a key process in cancer progression with relevance for EMT. EMT has been reported to be dependent on modulation of ion channels of sodium, potassium, and calcium in different cancer types, and inhibiting the activity of these ion channels has been proposed as a potential therapy against cancer progression [ [144] , [145] , [146] , [147] ]. Similarly, G1/S transition is a major checkpoint in the regulation of the cell cycle.…”
Section: Resultsmentioning
confidence: 99%
“…TRPV4 may regulate breast cancer metastasis by regulating cell flexibility and extracellular protein expression through calcium dependent AKT-E-cadherin signal axis 22 . Although TRPV3 is a member of TRP superfamily, through network analysis, TRPV3 related to epithelial mesenchymal transformation of breast cancer 8 , but the role and mechanism of TRPV3 in breast cancer have not fully clarified. We observed that TRPV3 upregulated in human breast cancer samples and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Ion channel disorder appeared to be responsible for the enhanced migration of cancer cells and ECM dysregulation [ 30 , 31 ]. Aberrant activation of Ca 2+ -permeable channels on the endoplasmic reticulum membrane and plasma membrane led to impulse Ca 2+ influx [ 32 ].…”
Section: Discussionmentioning
confidence: 99%